2021
DOI: 10.3389/fphys.2021.676512
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-Beta1 and Human Gingival Fibroblast-to-Myofibroblast Differentiation: Molecular and Morphological Modifications

Abstract: After oral mucosal injury, the healing response following specific steps that lead to wound closure and to tissue repair. Multiple cell populations are involved in this process; in particular, fibroblasts play a key role in the production of extracellular matrix (ECM). During wound healing the remodeling of ECM is a key stage to restore the tissue functionality through multifunctional fibroblast populations that are placed in the connective tissues of gingiva and periodontal ligament. Notably, a fibroblast sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Several cell types including the resident fibroblast, adipocytes, fibrocytes, monocytes, mesenchymal cells, and epithelial/endothelial cells can be differentiated into myofibrob-lasts [30]. During the normal wound healing process, myofibroblasts significantly disappear at the end of the process via apoptosis [30]. Their presence in the wound tissue is correlated with scar production.…”
Section: Wound Healing Process-general Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several cell types including the resident fibroblast, adipocytes, fibrocytes, monocytes, mesenchymal cells, and epithelial/endothelial cells can be differentiated into myofibrob-lasts [30]. During the normal wound healing process, myofibroblasts significantly disappear at the end of the process via apoptosis [30]. Their presence in the wound tissue is correlated with scar production.…”
Section: Wound Healing Process-general Aspectsmentioning
confidence: 99%
“…Their presence in the wound tissue is correlated with scar production. Moreover, myofibroblasts are involved in the production of ECM components and enhance the matrix elements' synthesis, such as laminin, glycosaminoglycans, and hyaluronic acid [30]. Marconi and co-workers observed that, in gingival tissue, during the wound healing process, cytokines and GFs stimulate the differentiation of resident fibroblasts into myofibroblasts [30].…”
Section: Wound Healing Process-general Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transforming growth factor-β (TGF-β), which is produced in the early stages of wound healing, is known to cause an increase in α-SMA expression through phosphorylation of Smad3 and plays a major role in myofibroblast differentiation [ 49 ]. Recently, Marconi and colleagues also showed that when human gingival fibroblasts (hGFs) are treated with TGFβ in vitro, they differentiate into myofibroblasts, determined by morphological and molecular modifications such as the induction of α-SMA, Vimentin, E-cadherin, β-catenin, and Smad 2/3 [ 50 ]. After the formation of actin-myosin contractile bundles, stress fibres, it is the neo-expression and incorporation of α-SMA that significantly augments the contractile activity of activated myofibroblasts [ 51 , 52 ].…”
Section: Gla-containing Ecm Proteinsmentioning
confidence: 99%